Unique nature conservation categories (IUCN 1900–2003) - Balogh, Dániel; Hegedüs, Csaba; Juhász, Vera; Kollár, Balázs; Meinhardt, Sarolta; Molnár, Attila; Paulin, Márton; Sáradi, Nóra; Schermann, Balázs; Sóki, Edina (JOURNAL OF LANDSCAPE ECOLOGY, 2018)
In this article we introduce the unique categories of conservation areas that are only present in a single country. These territories were established between 1900 and 2003, and have also undergone IUCN classification, and are thus legitimate categories. We present these classifications with their locations, and also consider, whether these were well thought out, or unnecessary. We take a look at their spread among the official IUCN categories, paired with the size of the territories. Moreover, we study their countries of origin, which shows that even though every continent has such areas, their spread is not even. Lastly, we select five of such places and characterize them, to shed light on the reasons behind the unique classifications.
Keywords: nature conservation history; rare categories; national categories